2013
DOI: 10.1007/s11669-013-0265-7
|View full text |Cite
|
Sign up to set email alerts
|

Phase Identification of Cu-In Alloys with 45 and 41.25 at.% In Compositions

Abstract: In this work, the thermal stability of Cu-In alloys with 45.0 and 41.2 at.% In nominal compositions was investigated by differential scanning calorimetry (DSC), scanning electron microscopy, wavelength dispersive spectroscopy, and in-situ synchrotron x-ray powder diffraction (S-PXRD) over a temperature range from 25 up to 400 °C. The studied samples are mainly composed of a Cu 11 In 9 phase together with minor amounts of the B phase (based on the NiAs-Ni 2 In type structure) and, in one of the samples, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…For the sample aer electrolysis, major peaks assigned to metallic Cu 11 In 9 , Cu 7 In 3 and Cu were observed, in addition to the peaks associated with the carbon substrate, consistent with the phase diagram of the Cu-In system. 43 It was conrmed that the CuInO 2 phase was reduced to form the metallic phase. The SEM image of the as-prepared sample in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the sample aer electrolysis, major peaks assigned to metallic Cu 11 In 9 , Cu 7 In 3 and Cu were observed, in addition to the peaks associated with the carbon substrate, consistent with the phase diagram of the Cu-In system. 43 It was conrmed that the CuInO 2 phase was reduced to form the metallic phase. The SEM image of the as-prepared sample in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the nature of the second metal or metal oxide situated in the vicinity of Cu appears to be paramount in the context of the CO2 reduction process. 43 It was confirmed that the CuInO2 phase was reduced to form the metallic phase. [39][40][41] Thus, the discrete nature of each component in the Cu-based system influenced the selectivity of the products from aqueous CO2 under identical conditions.…”
Section: Electrocatalytic Performance and Characterization Of Cu-in Cmentioning
confidence: 96%
“…31 Besides, the melting point of the IMC, i.e., Cu 11 In 9 (about 310 °C), is much higher than that of indium (156 °C), which means a much higher working temperature of the thermal interface materials. 32 Here, we tested the thermal conductivities of the porous material at various temperatures to evaluate its viability in different scenarios. It can be seen from Figure 2h that the thermal conductivity of porous copper slightly decreases from 43.0 W m −1 K −1 at 25 °C to 39.7 W m −1 K −1 at 225 °C, which suffers from higher-temperature-induced stronger phonon scattering.…”
Section: Resultsmentioning
confidence: 99%
“…The a‐Si solar cells are of low efficiency but proved to be more environmentally friendly PV cells. This uses less silicon and also does not contain the aluminum frame, but on the flip side, the efficiency is between 6% to 12% and less popular as they are harder to replace . Amorphous alloys of silicon and carbon (amorphous silicon carbide, also hydrogenated, a‐Si1 − xCx:H) are an interesting variant.…”
Section: Categories Of Pv Cellsmentioning
confidence: 99%